Short- and long-term prognosis in patients with unstable angina and anemia - T. Yu. Kalyuta; O. E. Tsareva; A. D. Trubetskov; Yu. G. Schwarz (Кардиоваскулярная терапия и профилактика)
Aim. To investigate correlation between anemia and long- and short-term prognosis in patients with unstable angina. Material and methods. The study included 96 patients (34 females), aged 63.3±10.3 years, with unstable angina. All patients received conservative treatment. Individuals with severe associated pathology and hemorrhages in anamnesis were excluded from the study. Anemia was diagnosed according to WHO criteria; unstable angina class was registered. Short-term, in-hospital prognosis assessment included registering severe, recurrent angina, myocardial infarction (MI), number of ischemic episodes during 24-hour ECG monitoring before discharge. Long-term prognosis was assessed during 6 post-discharge months: death, MI, and combined endpoint (cardiac death, MI, recurrent angina) were registered. Results. Anemia was diagnosed in 38 patients (39.58 %). Angina at rest was associated with lower mean hemoglobin (Hb) level and greater anemia prevalence (46%), comparing to the group of progressing effort angina (25%). Participants with prolonged angina episodes had significantly lower Hb level (122.23±13.3 g/l) than the others (130.9±13.56 g/l). Among patients with ischemic episodes at 24-hour ECG monitoring, anemia was registered in 50%, among individuals without such episodes – in 30.4%. Recurrent unstable angina during 6 post-discharge months was associated with higher anemia prevalence: 57.6% vs 21.05% in participants with better outcome. Logistic regression analysis demonstrated negative independent influence of anemia on combined endpoint. Conclusion. Patients with anemic syndrome were characterized by severe in-hospital course of unstable angina. Anemia was associated with increased risk of MI and recurrent unstable angina in the first 6 months after discharge.